2014
DOI: 10.1039/c4nr03560g
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence-assisted shear exfoliation of graphene using household detergent and a kitchen blender

Abstract: To facilitate progression from the lab to commercial applications, it will be necessary to develop simple, scalable methods to produce high quality graphene. Here we demonstrate the production of large quantities of defect-free graphene using a kitchen blender and household detergent. We have characterised the scaling of both graphene concentration and production rate with the mixing parameters: mixing time, initial graphite concentration, rotor speed and liquid volume. We find the production rate to be invari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
276
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(301 citation statements)
references
References 43 publications
21
276
2
2
Order By: Relevance
“…It is important to do this first as nanosheet dispersions can be very sensitive to surfactant content, perhaps more so than any other parameter. 37 To do this, figure 3A). We note that this behaviour is distinct to that observed for graphene produced by shear-exfoliation in a slightly different blender with a different surfactant, where we found the graphene concentration to depend on the ratio of Csurf /Ci rather than Csurf alone.…”
Section: The Effect Of Surfactant Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to do this first as nanosheet dispersions can be very sensitive to surfactant content, perhaps more so than any other parameter. 37 To do this, figure 3A). We note that this behaviour is distinct to that observed for graphene produced by shear-exfoliation in a slightly different blender with a different surfactant, where we found the graphene concentration to depend on the ratio of Csurf /Ci rather than Csurf alone.…”
Section: The Effect Of Surfactant Concentrationmentioning
confidence: 99%
“…Below, we will use this to measure the MoS2 concentration as a function of mixing parameters, in a manner similar to that recently reported for shear-exfoliated graphene. 35,37 However, in addition to concentration information, it has recently been shown that the extinction spectrum of MoS2 nanosheets carries information about both the mean nanosheet length and thickness. 39 The length effects are due to the effect of nanosheet edges on the spectral profile while quantum confinement effects result in well-defined shifts in A-exciton position with nanosheet thickness.…”
Section: Initial Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, shear mixer was introduced to exfoliate the graphite into individual graphene nanosheets [3,4,[38][39][40]. Because the oxygen-containing groups binding on carbon atoms will increase the interlayer spacing of graphite oxide, and make the layered graphite oxide easier to cleave [10,41].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been growing interest in exfoliation of layered materials to produce two-dimensional (2D) nanosheets, such as graphene [2][3][4][5][6], graphene oxide (GO) [1,[7][8][9][10], etc. GO has recently attracted substantial interest as a possible intermediate for the preparation of graphene [11][12][13] and metal oxide/graphene nanocomposites [14][15][16].…”
Section: Introductionmentioning
confidence: 99%